Prenatal Diagnosis of Cardiac Rhabdomyoma and Cortical Tubers Proven as Tuberous Sclerosis Complex - Sri Sai Lakshmi, Bacchu Jagannatha; Chintala, Jitender Reddy (Journal of Fetal Medicine, 2025)
We report a case of multiple fetal cardiac rhabdomyomas and cortical based echogenic masses in a primigravida, detected at 27 weeks of gestation. Prenatal genetic testing revealed a heterozygous 23 base pair deletion of the TSC2 gene. Postnatally, the child presented with seizures and showed multiple bilateral periventricular and subependymal hamartomas with cortical and subcortical tubers on magnetic resonance imaging (MRI). Multiple hypomelanotic macules were seen on the back, chest, and eyelids. Rhabdomyomas are the most common prenatally detected cardiac tumor. They appear as a homogeneous echogenic mass on ultrasound and usually are asymptomatic. In 10% of cases, they can cause complications such as outflow tract obstruction, hydrops, arrhythmia, cardiac failure, and intrauterine death. There is a strong association between cardiac rhabdomyoma and tuberous sclerosis, which has an autosomal dominant inheritance pattern and multisystem involvement. Detection of rhabdomyoma should prompt further evaluation to look for other systemic associations by fetal MRI. Genetic counseling and prenatal testing are advised to confirm the diagnosis, to improve the management of other related symptoms, and to plan future pregnancies.
Keywords: cardiac neoplasm; cortical tubers; fetal ultrasound; heart; prenatal diagnosis; rhabdomyoma; tuberous sclerosis complex